The Political and Economic Consequences of Nationalist Protest in China: The 2012 Anti-Japanese Demonstrations. (31st October 2018) - Foley, Kevin; Wallace, Jeremy L.; Weiss, Jessica Chen
Abstract: What are the consequences of nationalist unrest? This paper utilizes two original datasets, which cover 377 city-level anti-Japanese protests during the 2012 Senkaku/Diaoyu Island crisis and the careers of municipal leaders, to analyse the downstream effects of nationalist unrest at the subnational level. We find both political and economic consequences of China's 2012 protest demonstrations against Japan. Specifically, top Party leaders in cities that saw relatively spontaneous, early protests were less likely to be promoted to higher office, a finding that is consistent with the widely held but rarely tested expectation that social instability is punished in the Chinese Communist Party's cadre evaluation system. We also see a negative effect of nationalist protest on foreign direct investment (FDI) growth at the city level. However, the lower promotion rates associated with relatively spontaneous protests appear to arise through political rather than economic channels. By taking into account data on social unrest in addition to economic performance, these results add to existing evidence that systematic evaluation of leaders' performance plays a major role in the Chinese political system. These findings also illuminate the dilemma that local leaders face in managing popular nationalism amid shifting national priorities. 摘要: 爱国主义抗议有哪些后果? 通过分析包含 377 次反日示威和市级领导简历的两组原创数据库, 此论文探讨反日示威在次国家层面的后续效应。我们发现 2012 年的反日示威确实导致了政治和经济两方面的后果。具体而言, 在那些有比较自发的、发生时间较早的抗议游行的城市, 市级领导晋升的可能性相对更低。这一观察符合一种广泛存在、但很少证实的猜测, 即维稳方面的政绩已成为中国共产党干部考核制度的重要内容。作者也发现, 爱国主义抗议对地方吸引外商直接投资 (FDI) 有负面影响。但是, 自发的爱国主义示威似乎是通过政治的、而非经济的渠道对市级领导的晋升产生负面影响。通过将社会动乱数据与经济绩效数据相结合, 此研究进一步证实了部绩效系统考核制度在中国政治体系中的主要作用。此研究也有助于理解地方领导在面临国家利益优先次序变动的情况下如何管控爱国主义浪潮的政治困境。